2013
DOI: 10.1007/s11010-013-1660-4
|View full text |Cite
|
Sign up to set email alerts
|

Expression of adropin in rat brain, cerebellum, kidneys, heart, liver, and pancreas in streptozotocin-induced diabetes

Abstract: We have investigated how diabetes affects the expression of adropin (ADR) in rat brain, cerebellum, kidneys, heart, liver, and pancreas tissues. The rats in the diabetic group were administered an intraperitoneal (i.p.) injection of a single dose of 60 mg/kg streptozotocin (STZ) dissolved in a 0.1 M phosphate-citrate buffer (pH 4.5). The rats were maintained in standard laboratory conditions in a temperature between 21 and 23 °C and a relative humidity of 70 %, under a 12-h light/dark cycle. The animals were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
116
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(122 citation statements)
references
References 34 publications
6
116
0
Order By: Relevance
“…5D). A previous study has demonstrated that adropin is detected at granular and Purkinje cells in the cerebellum (37). Unfortunately, we could not find a suitable antiadropin antibody to perform a similar immunohistochemical FIGURE 5.…”
Section: Discussionmentioning
confidence: 99%
“…5D). A previous study has demonstrated that adropin is detected at granular and Purkinje cells in the cerebellum (37). Unfortunately, we could not find a suitable antiadropin antibody to perform a similar immunohistochemical FIGURE 5.…”
Section: Discussionmentioning
confidence: 99%
“…However, the source of the exercise training-induced increase in serum adropin levels remains unclear. Adropin is expressed in vascular endothelial cells, as well as in brain, heart, kidney, liver, pancreas, skeletal muscle, and small intestine (2,32). An in vitro study showed that adropin treatment promotes NO production from the human umbilical vein endothelial cells in a time-dependent manner, mediated via phosphorylation of eNOS protein (20).…”
Section: Discussionmentioning
confidence: 99%
“…Adropin consists of 76 amino acids and is encoded by a gene, Energy Homeostasis Associated (Enho) (16), and expressed in multiple tissues, including the brain, heart, kidney, liver, pancreas, skeletal muscle, and small intestine (2,32). Circulating adropin level decreases with age (7).…”
mentioning
confidence: 99%
“…However, all these studies are not specific to the cerebellum. Research studies related to the cerebellum are very few to our knowledge (1,2,4,7,8).…”
Section: Discussionmentioning
confidence: 99%